Fabrication of High-Performance Thin-Film Composite Nanofiltration Membrane by Dynamic Calcium-Carboxyl Intra-Bridging during Post-Treatment - Hongyi Han; Ruobin Dai; Zhiwei Wang (Membranes, 2020)
Widespread applications of nanofiltration (NF) and reverse osmosis (RO)-based processes for water purification and desalination call for high-performance thin-film composite (TFC) membranes. In this work, a novel and facile modification method was proposed to fabricate high-performance thin-film composite nanofiltration membrane by introducing Ca2+ in the heat post-treatment. The introduction of Ca2+ induced in situ Ca2+-carboxyl intra-bridging, leading to the embedment of Ca2+ in the polyamide (PA) layer. This post modification enhanced the hydrophilicity and surface charge of NF membranes compared to the pristine membrane. More interestingly, the modified membrane had more nodules and exhibited rougher morphology. Such changes brought by the addition of Ca2+ enabled the significant increase of water permeability (increasing from 17.9 L·m−2·h−1·bar−1 to 29.8 L·m−2·h−1·bar−1) while maintaining a high selectivity (Na2SO4 rejection rate of 98.0%). Furthermore, the intra-bridging between calcium and carboxyl imparted the NF membranes with evident antifouling properties, exhibiting milder permeability decline of 4.2% (compared to 16.7% of NF-control) during filtration of sodium alginate solution. The results highlight the potential of using Ca2+-carboxyl intra-bridging post-treatment to fabricate high-performance TFC membranes for water purification and desalination.